2014
DOI: 10.5194/gmd-7-1483-2014
|View full text |Cite
|
Sign up to set email alerts
|

A novel model evaluation approach focusing on local and advected contributions to urban PM<sub>2.5</sub> levels – application to Paris, France

Abstract: Abstract. Aerosol simulations in chemistry transport models (CTMs) still suffer from numerous uncertainties, and diagnostic evaluations are required to point out major error sources. This paper presents an original approach to evaluate CTMs based on local and imported contributions in a large megacity rather than urban background concentrations. The study is applied to the CHIMERE model in the Paris region (France) and considers the fine particulate matter (PM 2.5 ) and its main chemical constituents (elementa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(77 citation statements)
references
References 73 publications
(75 reference statements)
4
73
0
Order By: Relevance
“…The overestimation of secondary organic aerosol with the CHIMERE standard scheme is a new feature (Bessagnet et al, 2008 ;Hodzic and Jimenez, 2011 ;Petetin et al, 2014). A previous comparison of CHIMERE with organic aerosol simulations using the same scheme and coupled to MEGAN biogenic emissions, resulted in a good close to the western Mediterranean basin (Montelibretti, Italy).…”
Section: Comparison Of Pm1 Total Organic Aerosols Concentrationmentioning
confidence: 99%
See 2 more Smart Citations
“…The overestimation of secondary organic aerosol with the CHIMERE standard scheme is a new feature (Bessagnet et al, 2008 ;Hodzic and Jimenez, 2011 ;Petetin et al, 2014). A previous comparison of CHIMERE with organic aerosol simulations using the same scheme and coupled to MEGAN biogenic emissions, resulted in a good close to the western Mediterranean basin (Montelibretti, Italy).…”
Section: Comparison Of Pm1 Total Organic Aerosols Concentrationmentioning
confidence: 99%
“…The CHIMERE model has been previously validated for different parts of the world Solazzo et al, 2012 ;Borrego et al, 2013 ;Berezin et al, 2013 ;Petetin et al, 2014 ;Rea et al, 2015 ;;Konovalov 30 et al, 2015 ;Mallet et al, 2016). The data set presented in section 3 is used for model validation.…”
Section: Model Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…On average, the NO x regional background roughly accounts for 15-25 % and 15-30 % of the levels in Paris for observations and simulations, respectively. From 1-year measurements during the PARTICULES campaign (Bressi et al, 2013), it has been found that the BC regional background contributes to about a third to the annual BC urban background average in Paris, and that this fraction is probably underestimated by the CHIMERE model (Petetin et al, 2014). However, this uncertainty source remains difficult to quantify more precisely.…”
Section: Approach No 1: Emissions Evaluation From Surface Measurementsmentioning
confidence: 99%
“…As a consequence, air quality models (AQMs), despite significant progress, still have difficulties to quantitatively reproduce the observed particulate matter (PM) levels and gradients, and continue to underestimate the formation of SOA in the troposphere, from cities to remote areas (Shrivastava et al, 2011;Ervens et al, 2011;Petetin et al, 2014). In this regard, the chemistry of organics in the aqueous condensed phase remains poorly characterized.…”
Section: Lemaire Et Al: Oligomer Formation In the Tropospherementioning
confidence: 99%